Targeting the IL-17 Pathway in Inflammatory Disorders - Chu, Cong-Qiu.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Adis, 2017)
This book provides an overview of the discovery and structure of IL-17, including its pathogenesis and role in chronic inflammation and autoimmunity. To capture the latest developments and product approvals the book also discusses the therapeutic advances and looks at emerging therapies targeting the IL-17 pathway. IL-17 is a pro-inflammatory cytokine that has a key role in inflammation, autoimmunity, and host defense in a number of inflammatory disorders such as rheumatoid arthritis, psoriatic arthritis and psoriasis, ankylosing spondylitis, multiple sclerosis, and inflammatory bowel disease. The discovery of the IL-17-Th17 pathway has seen exciting development in the field of immunology and inflammation research, which has led to a number of recent regulatory approvals.
Introduction -- Overview of IL-17 family.-Il-17 in host defense -- Th17 cells: differentiation and regulation -- The role of the IL-17/Th17 pathway in the pathogenesis of autoimmune inflammatory diseases -- Therapeutic applications: strategies and molecules targeting the IL-17/Th17 pathway -- Concluding remarks.
Keywords: Medicine; Dermatology; Public health; Rheumatology; Primary care (Medicine).; Pharmacotherapy; Medicine & Public Health; Rheumatology; Dermatology; Pharmacotherapy; Primary Care Medicine; Public health